Palliative care and quality of life in neuro-oncology - Mummudi, Naveen (Faculty of 1000 Ltd, 2014)
Health-related quality of life has become an important end point in modern day clinical practice in patients with primary or secondary brain tumors. Patients have unique symptoms and problems from diagnosis till death, which require interventions that are multidisciplinary in nature. Here, we review and summarize the various key issues in palliative care, quality of life and end of life in patients with brain tumors, with the focus on primary gliomas.